LYSIS OF ESCHERICHIA COLI BY SULFHYDRYL-BINDING REAGENTS - Schaechter, M. (1962)
Schaechter, M. (College of Medicine, University of Florida, Gainesville) and K. Santomassino. Lysis of Escherichia coli by sulfhydryl-binding reagents. J. Bacteriol. 84:318–325. 1962—Washed suspensions of gram-negative rods were lysed by low concentrations of some sulfhydryl-binding and oxidizing reagents, but not by reducing agents. Some kinetic aspects of this phenomenon were studied with p-chloromercuribenzoate and Escherichia coli B/r. Structures resulting from the action of this reagent consisted of impure cell walls. These could be purified by treatment with trypsin. Cell walls prepared mechanically and cell membranes obtained by lysing protoplasts were not overtly affected by this chemical.